2016
DOI: 10.2337/dc16-0411
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Hypoglycemia and Physical Activity in Children With Diabetes: New Insights by Continuous Glucose Monitoring and Accelerometry

Abstract: Figure 1-Risk of nocturnal hypoglycemia correlated to bedtime glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 6 publications
0
20
0
2
Order By: Relevance
“…An advantage of the approach presented in this work is the inclusion of features related with physical activity as input for the prediction models. It has already been shown that daytime physical activity is strongly related with NH [38][39][40]; however, previous investigations intended for NH prediction did not consider such information [28,41]. In our proposal, physical activity data were collected by the wristband.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of the approach presented in this work is the inclusion of features related with physical activity as input for the prediction models. It has already been shown that daytime physical activity is strongly related with NH [38][39][40]; however, previous investigations intended for NH prediction did not consider such information [28,41]. In our proposal, physical activity data were collected by the wristband.…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents using an isCGM should perform a scan at least twice during the nocturnal period (e.g. at 01:00 hours and 04:00 hours) due to the increased risk of nocturnal hypoglycaemia [101][102][103][104] (D), especially after exercise [81,[104][105][106] (D). Parents or other care providers can be alerted using the remote monitoring function within CGMs, which can support parents in their effort to avoid nocturnal hypoglycaemia in children [91] (D).…”
Section: Children and Adolescents With Type 1 Diabetesmentioning
confidence: 99%
“…Fear of hypoglycemia is the most common barrier to physical activity for children/adolescents and adults with T1D [43, 5255], and several studies have demonstrated increased risk of hypoglycemia resulting from exercise [5658]. Lack of time and work schedules for adults and parents are also barriers [53, 59].…”
Section: Physical Activity and Individuals With T1dmentioning
confidence: 99%